In vivo deficiency of both C/EBPβ and C/EBPε results in highly defective myeloid differentiation and lack of cytokine response. - Tadayuki Akagi; Nils H Thoennissen; Ann George; Gay Crooks; Jee Hoon Song; Ryoko Okamoto; Daniel Nowak; Adrian F Gombart; H Phillip Koeffler (PLoS ONE)
The CCAAT/enhancer binding proteins (C/EBPs) are transcription factors involved in hematopoietic cell development and induction of several inflammatory mediators. Here, we generated C/EBPβ and C/EBPε double-knockout (bbee) mice and compared their phenotypes to those of single deficient (bbEE and BBee) and wild-type (BBEE) mice. The bbee mice were highly susceptible to fatal infections and died within 2-3 months. Morphologically, their neutrophils were blocked at the myelocytes/metamyelocytes stage, and clonogenic assays of bone marrow cells indicated a significant decrease in the number of myeloid colonies of the bbee mice. In addition, the proportion of hematopoietic progenitor cells [Lin(-)Sca1(+)c-Kit(+)] in the bone marrow of the bbee mice was significantly increased, reflecting the defective differentiation of the myeloid compartment. Furthermore, microarray expression analysis of LPS- and IFNγ-activated bone marrow-derived macrophages from bbee compared to single knockout mice revealed decreased expression of essential immune response-related genes and networks, including some direct C/EBP-targets such as Marco and Clec4e. Overall, the phenotype of the bbee mice is distinct from either the bbEE or BBee mice, demonstrating that both transcription factors are crucial for the maturation of neutrophils and macrophages, as well as the innate immune system, and can at least in part compensate for each other in the single knockout mice.